No Refuge Here: Iraqis Flee, but Where? - Huff-Hannon, Joseph (Dissent (00123846))
The Bush administration refuses to resettle significant numbers of Iraqi refugees, using current U.S. refugee and immigration policy to effectively keep them out of sight and out of mind. The government has linked refugee policy to foreign policy, typically refusing those “undeserving” refugees fleeing war and persecution in countries with governments supported by the U.S. as distinct from “deserving” refugees fleeing states with leftist governments, stormy diplomatic relations with the U.S., or both. Until recently, the U.S. had a proud history of admitting refugees, and it should now emulate this by doing more to assist both those Iraqis trapped in legal limbo in the Middle East and those who have a sound reason to think that the U.S. owes them sanctuary.